2005
DOI: 10.1189/jlb.1003456
|View full text |Cite
|
Sign up to set email alerts
|

TNFR1-induced sphingomyelinase activation modulates TCR signaling by impairing store-operated Ca2+ influx

Abstract: Tumor necrosis factor alpha (TNF-alpha) is a potent, pleiotrophic cytokine, which is proinflammatory but can also suppress T lymphocyte function. In chronic inflammatory disease such as rheumatoid arthritis, exposure of T cells to TNF-alpha alters their ability to mount a response by modulating the T cell receptor (TCR) signaling pathway, but the mechanisms involved remain obscure. Here, we investigated the specific role of TNF receptor 1 (TNFR1) signaling in the modulation of the TCR signaling pathway. We obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 55 publications
1
35
1
Order By: Relevance
“…different concentrations of human recombinant TNFĪ±, which has been shown to be recognized by the murine TNFĪ±RI but not TNFĪ±RII. 31 Medium and cells were collected. The medium was cleared from dead cells by centrifugation at 80 x g, while the cells were homogenated in the buffer listed below.…”
Section: Materials N-hexanoyl-((n-(7-nitrobenz-2-oxa-13-diazol-4-ylmentioning
confidence: 99%
“…different concentrations of human recombinant TNFĪ±, which has been shown to be recognized by the murine TNFĪ±RI but not TNFĪ±RII. 31 Medium and cells were collected. The medium was cleared from dead cells by centrifugation at 80 x g, while the cells were homogenated in the buffer listed below.…”
Section: Materials N-hexanoyl-((n-(7-nitrobenz-2-oxa-13-diazol-4-ylmentioning
confidence: 99%
“…In particular, it was demonstrated that ceramide inhibits the potassium channel Kv1.3 and calcium releaseactivated calcium channels in lymphocytes (32,67,100,151). Both channels are central for activation, differentiation, proliferation, and regulation of apoptosis.…”
Section: Function Of Ceramide-enriched Membrane Domainsmentioning
confidence: 99%
“…The tissue was minced and immediately homogenized, according to a previously published technique with minor modifications. 31 Cells were incubated for 30 min on ice with FITC-conjugated anti-mouse CD34 (RAM34; eBioscience, San Diego, CA) and PE-conjugated anti-mouse Flk-1 (Avas12ā£1; BD Biosciences, Rockville, MD) or with FITC-conjugated anti-mouse CD117 (c-Kit; BD Biosciences) and PE-conjugated anti-mouse CD150 (eBioscience). After incubation, cells were washed with PBS and fixed in 4% paraformaldehyde.…”
Section: Facs Analysismentioning
confidence: 99%